2019
DOI: 10.1186/s13071-019-3833-9
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of mice with a recombinant novel cathepsin B inhibits Trichinella spiralis development, reduces the fecundity and worm burden

Abstract: BackgroundTrichinella spiralis is a major zoonotic tissue-dwelling nematode, which is a public health concern and a serious hazard to animal food safety. It is necessary to exploit an anti-Trichinella vaccine to interrupt the transmission of Trichinella infection among animals and from animals to humans. The purpose of the present study was to characterize the novel T. spiralis cathepsin B (TsCB) and to evaluate the immune protection elicited by immunization with recombinant TsCB (rTsCB).MethodsThe complete cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 69 publications
6
34
0
Order By: Relevance
“…In recent years, some protein molecules from various T. spiralis lifecycle stages have been characterized and expressed, and their immune protection was also evaluated, such as paramyosin (Ts-Pmy) from an adult cDNA library [9], TspGST and fructose-1,6-bisphosphate aldolase (Ts-FBPA) from the T. spiralis draft genome with high expression at the ML stage [33,68], Ts31 from the ML ES proteins [54], serine protease (TsSP) from IIL and ML surface proteins [55], and cathepsin B (TsCB) from the T. spiralis draft genome [56]. However, when these recombinant proteins were used for vaccinating mice, they exhibited only 36.2-53.50% ML reduction following T. spiralis challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some protein molecules from various T. spiralis lifecycle stages have been characterized and expressed, and their immune protection was also evaluated, such as paramyosin (Ts-Pmy) from an adult cDNA library [9], TspGST and fructose-1,6-bisphosphate aldolase (Ts-FBPA) from the T. spiralis draft genome with high expression at the ML stage [33,68], Ts31 from the ML ES proteins [54], serine protease (TsSP) from IIL and ML surface proteins [55], and cathepsin B (TsCB) from the T. spiralis draft genome [56]. However, when these recombinant proteins were used for vaccinating mice, they exhibited only 36.2-53.50% ML reduction following T. spiralis challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The AWs were recovered from the small intestines of ten mice of each group at 7 dpi [54,55]. The ML were collected from an additional ten mice at 42 dpi by digesting the infected mouse striated muscles [56]. Moreover, the length of adult females was measured by microscopy.…”
Section: Oral Larva Challenge Infection and Assessment Of Immune Protmentioning
confidence: 99%
“…To assess the cytotoxic activity of anti-TsT immune serum, the ADCC test was conducted in this study. The results showed that anti-rTsT immune serum promoted the adhering and killing of the PECs to the NBL, and the cytotoxic activity was dose-dependent of anti-rTsT antibodies, suggesting that anti-TsT IgG participated in the killing and destruction of newborn larvae by the ADCC fashion [ 56 , 64 ]. The sera used in this study were not heat-inactivated to inactivate complement.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ML, IIL and AW were embedded in paraffin, 3-µm thick cross-sections were prepared using a microtome. Expression and tissue localization of native TsT in various T. spiralis stages were determine with IIFT [ 16 , 56 ]. In brief, the whole worms and worm cross-sections were blocked using 1% BSA in PBS and then incubated with various sera (1:10; anti-rTsT serum, infection serum or pre-immune serum) at 37 °C for 2 h. Following washes with PBS, worms and cross-sections were stained with anti-mouse IgG conjugated FITC (1:100; Santa Cruz Biotech, Dallas, Texas, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the worms were embedded in paraffin, and 3-µm-thick cross-sections were cut with a microtome. The expression and worm tissue location of native TsSerp in diverse T. spiralis stages were observed using IFA as previously reported [46,47]. Briefly, intact whole nematodes and cross-sections were blocked with 5% normal goat serum in PBS and then probed at 37 °C for 2 h with 1:10 dilutions of various sera (anti-rTsSerp serum, infection serum or pre-immune serum).…”
Section: Immunofluorescence Assay (Ifa)mentioning
confidence: 99%